Digital economy, industrial agglomeration, and green innovation efficiency: Empirical analysis based on Chinese data - Jiamin Liu; Yongheng Fang; Yabing Ma; Yihan Chi (Journal of Applied Economics, 2024)
This study measures and analyzes the spatial characteristics of the relevant indices by constructing an evaluation index system. The SBM-DEA model and Tobit regression model were used to empirically test the influence relationship between digital economy, industrial agglomeration, and green innovation efficiency development. The study results show (1) the development level of China's digital economy, industrial agglomeration and green innovation efficiency shows a heterogeneous character of "high in the east and low in the west" at the spatial level. (2) the positive effect of China's digital economy and diversified industrial agglomeration on the development of green innovation efficiency. (3) Among other influencing factors, trade openness and labor quality have a significant impact on improving the efficiency of green innovation.Therefore, this study puts forward suggestions to strengthen the construction of new infrastructures, correctly guide the collaborative industrial agglomeration, and strengthen the exchange of information among enterprisers.
Keywords: 330; Digital economy; green innovation efficiency; industrial agglomeration